2017
DOI: 10.5430/jms.v8n5p30
|View full text |Cite
|
Sign up to set email alerts
|

University Students Usage of Facebook: The Case of Obtained Gratifications and Typology of Its Users

Abstract: This paper presents and discusses the results from the designed quantitative self-report questionnaire. It addresses two main research objectives: first, to contribute to the uses and gratifications research by exploring the gratifications that research participants who belong to an Islamic culture obtain from using Facebook, and second, to inform theoretical and empirical media and communications research through proposing a typology of users based on their obtained gratifications, usage variables, and demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A content analysis of status updates also revealed that 16 different status themes are posted ranging from simple greetings to the discussion of social and political issues (Aljasir et al, 2017b). The findings from this research shows how the adoption of the theoretical framework and methodological approach in this research can extend current knowledge and take an important step toward explaining what Saudi university students obtain from their usage of Facebook and its potential costs.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…A content analysis of status updates also revealed that 16 different status themes are posted ranging from simple greetings to the discussion of social and political issues (Aljasir et al, 2017b). The findings from this research shows how the adoption of the theoretical framework and methodological approach in this research can extend current knowledge and take an important step toward explaining what Saudi university students obtain from their usage of Facebook and its potential costs.…”
Section: Resultsmentioning
confidence: 88%
“…The results of another pervious research had indicated that discussing political and social issues were important gratifications for the students (Aljasir et al, 2017b). Thus, this research seeks to understand the role of Facebook in enabling more open discussions and other users' reactions to such usage.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-processing task: Compiling the comments into one Microsoft Word documents. Sentiment Analyses: using two different strategies, manual and computing have implemented in this research [1,4,[23][24][25][26].…”
Section: Methodsmentioning
confidence: 99%